Lineages of Islamic Extremism in Egypt: Ikhwan al-Muslimun, State Violence and the Origins of Radical Politics - Ali Munhanif; M. Dahlan (Al-Jami'ah Research Centre, 2018)
This article examines why an Islamic organization appeal into radical behavior? Focusing on Ikhwan al-Muslimun (IM) and its splinter groups in Egypt, this article seeks to highlight historical-institutional underpinnings of when and how political Islam faced obstacles to enter pragmatic politics. Political experiences of the IM in the 1950s and the institutional structures created by Nasser’s regime in the early 1960s have shaped a condition of uncertainty that constrained Islamist activists to twart moderation. Islamist thinkers such as Sayyid Qutb exploited the fear of Nasserism and new emerging state institutions, to convince many members that they were threatened by the current regime. Initiatives to embrace radical ideology and actions have become dominant frameworks in the IM. The extent to which this radical ideology may develop is not only because of these institutional constraints, but also because of the absence of pragmatic-minded leaders who appealed with non-violence ideas to integrate Islamic agenda in institutional opportunities. [Tulisan ini membahas organisasi Islam yang cenderung menjadi radikal, studi kasus Ikhwan al-Muslimun (IM) dan pecahannya di Mesir, dengan mengulas secara organisasional historis disaat Islam politik tersebut mendapat rintangan ketika memasuki politik praktis. Pengalaman politik IM tahun 1950an dan 1960an saat dibawah rezim Nasser telah membawa ketidakpastian dan yang menyebabkan para aktifis menjauhi sikap moderat. Seorang Sayyid Qutb pun mengangkat ketakutan pada kekuasaan rezim Nasser untuk meyakinkan massa pada sebuah ancaman baru. Cara berpikir dan bertindak radikal telah menjadi pilihan yang dominan bagi anggota IM. Kesuburan paham radikal tersebut dimungkinkan karena tidak hanya adanya tekanan organisasional, tetapi juga tiadanya tokoh politik yang mendorong pendekatan non kekerasan dalam integrasikan agenda politik dengan peluang organisasioanal.]